Establishing Critical Thinking Course for High School Students in China: A Literature Review in Pedagogy Field (Proceedings of the International Conference on Education, 2019)
Abstract: This review synthesizes researches on students’ critical thinking (CT) abilities from school education in different contexts. It examines factors related to the importance of CT skills to students worldwide, identifies the current statues of the CT skills of students in China, and describes practical principles in real teaching scenarios. A total of 17 studies met the inclusion criteria. The key findings from the review are (a) massive worldwide investigations have offered various proposals and emphasized the significance of CT throughout the history; (b) Chinese students still generally undertake the gloomy image of CT capabilities; (c) an integration of a CT course to the curricula in a regular basis and a design of inquiry-based lesson plan need to be adopted in schools. The finding indicates that setting a CT course in high school can potentially assist students and schools to achieve the goals. For future research, a new curriculum for Chinese high schools to improve Chinese students’ CT abilities needs to be determined.Keywords: Critical thinking, China, high school, students
Keywords: Critical thinking; China; student; high school